KHAMAR DALAM PANDANGAN MASYARAKAT MUSLIM DAN NON MUSLIM DI DESA SIMPANG SEMADAM KABUPATEN ACEH TENGGARA - Siregar, M. Sukron; Utomo, Wahyu Wiji (Studia Sosia Religia, 2023)
The aim of this research is to find out the views of the Muslim and non-Muslim communities in Simpang Semadam Village regarding wine/tuak and what factors are obstacles in the effectiveness of implementing Qanun jinayat regarding wine and the like in Simpang Semadam Village. This research is a qualitative field research type using a phenomenological approach. The phenomenological approach is used to understand clearly and in more detail the problem being studied and also to describe how a person experiences interacting with each other and the surrounding environment. The results obtained from this research are that the view of the Muslim community in Simpang Semadam Village regarding wine and similar things always leads to negative things and considers palm wine to be unclean and haram for consumption. The view of the non-Muslim (Christian) Simpang Semadam community regarding the drink khamar, namely palm wine, is a traditional drink which has good properties for the body and is not haram and is also not an unclean item and is permissible to drink as long as you don't get drunk because getting drunk is something that is prohibited by the Christian religion. . After researching, it turns out that different views regarding khamar and the like cannot be separated from religious, social and cultural influences which make it difficult to implement the qanun jinayat regarding khamar in Simpang Semadam Village. The main factor is the mix of cultures and associations and habits between Muslims and non-Muslims who have different views on palm wine, so that the habit of drinking palm wine has seeped into people's lives in Simpang Semadam Village.